Analisis Kewajiban Upah Kerja Lembur pada Dinas Ketenagakerjaan UPT Wilayah I Sumatera Utara - Dhea Putri Andini; Saparuddin Siregar (Universitas Muhammadiyah Enrekang, 2022)
The objective of this study was to ascertain whether the Service of Manpower UPT I in the North Sumatra Region was required to pay overtime wages.At the Service of Manpower UPT I for the North Sumatra Region, direct interviews, observation, and documentation were used as data collection methods for the qualitative research method.According to the findings of the study, the practice of giving overtime pay from each company each has a system for paying overtime wages, but it is still not based on the rules that are set out in the Labor Law. This shows that the implementation of the obligation to pay overtime for workers who exceed their working hours at the Service of Manpower UPT I Region of North Sumatra, as well as the distribution of overtime pay given by the company to workers, is not in accordance with the Laws and Regulations.